The reduced form of coenzyme Q10 mediates distinct effects on cholesterol metabolism at the transcriptional and metabolite level in SAMP1 mice - Schmelzer, Constance; Okun, Jürgen G.; Haas, Dorothea; Higuchi, Keiichi; Sawashita, Jinko; Mori, Masayuki; Döring, Frank (IUBMB life, 2010)
Studies in humans and mice indicate a role for coenzyme Q10 (CoQ10) in gene expression. To analyze this function in relation to metabolism, SAMP1 mice were supplemented with the reduced (ubiquinol) or oxidized (ubiquinone) form of CoQ10 (500 mg/kg BW/d) for 14 months. Microarray analyses in liver tissues of SAMP1 mice identified 946 genes as differentially expressed between ubiquinol-treated and control animals (≥1.5-fold, P < 0.05). Text mining analyses revealed for a part of the ubiquinol-regulated genes, a functional connection in PPARα and LXR/RXR signalling pathways. Because these pathways are involved in cholesterol homeostasis, relevant metabolites were determined by gas chromatography/mass spectrometry (GC/MS). We found a significant increase of desmosterol (2.0-fold, P < 0.001) in the liver of ubiquinol-supplemented SAMP1 mice when related to control animals. In agreement, cholesterol concentrations were also distinctly increased (1.3-fold, P = 0.057). The Q10H2-induced PPARα and LXR/RXR gene expression signatures and effects on cholesterol metabolism were not apparent for the oxidized form of CoQ10. In conclusion, the reduced form of CoQ10 mediates distinct effects on cholesterol metabolism at the transcriptional and metabolite level in SAMP1 mice. © 2010 IUBMB IUBMB Life, 2010